Hepatic PPARα Is Destabilized by SIRT1 Deacetylase in Undernourished Male Mice - Suh, Ji Ho; Kim, Kang Ho; Conner, Margaret E.; Moore, David D.; Preidis, Geoffrey A. (Frontiers in Nutrition, 2022)
The nutrient sensing nuclear receptor peroxisome proliferator-activated receptor-α (PPARα) regulates the host response to short-term fasting by inducing hepatic transcriptional programming of ketogenesis, fatty acid oxidation and transport, and autophagy. This adaptation is ineffective in chronically undernourished individuals, among whom dyslipidemia and hepatic steatosis are common. We recently reported that hepatic PPARα protein is profoundly depleted in male mice undernourished by a low-protein, low-fat diet. Here, we identify PPARα as a deacetylation target of the NAD-dependent deacetylase sirtuin-1 (SIRT1) and link this to the decrease in PPARα protein levels in undernourished liver. Livers from undernourished male mice expressed high levels of SIRT1, with decreased PPARα acetylation and strongly decreased hepatic PPARα protein. In cultured hepatocytes, PPARα protein levels were decreased by transiently transfecting constitutively active SIRT1 or by treating cells with the potent SIRT1 activator resveratrol, while silencing SIRT1 increased PPARα protein levels. SIRT1 expression is correlated with increased PPARα ubiquitination, suggesting that protein loss is due to proteasomal degradation. In accord with these findings, the dramatic loss of hepatic PPARα in undernourished male mice was completely restored by treating mice with the proteasome inhibitor bortezomib. Similarly, treating undernourished mice with the SIRT1 inhibitor selisistat/EX-527 completely restored hepatic PPARα protein. These data suggest that induction of SIRT1 in undernutrition results in hepatic PPARα deacetylation, ubiquitination, and degradation, highlighting a new mechanism that mediates the liver’s failed adaptive metabolic responses in chronic undernutrition.